Analysis of liquid film flow in between two different plates - Wan Mohd Hasrol, Wan Hasan (2016)
In flip chip technology, analysis of underfill flow between chip and substrate are important to prevent the chip from breaking. In other words, the welded solder balls in the packaged chip, underfill epoxy is filled into the gap between a chip and a substrate. It is because to prevent cracks on the solder bump and electrical failure resulting from thermal fatigue. This project focuses on analysis liquid film flow in between two different plates. The filling time will be analyzed to estimate the flow behavior between two parallel plates and flow pattern of liquid to fulfill entire plate. This experimnet uses four different materials which glass, perspex, aluminum and tile with dimension 25mm x 25mm for lower plates. For upper plate is fixed by using glass also with dimension 25mm x 25mm. Software Free Video to JPG Converter used to identify the time taken to fulfill and software Adobe Photoshop to calculate the distance travelled of liquid and to visualize the flow pattern during to fulfill entire plate. Glass-tile present high filling time due to its properties of surface roughness and under 300s of filling time, materials with lowest surface roughness travelled in longest distance.